Women and Muslim Family Laws in Arab States A Comparative Overview of Textual Development and Advocacy - Welchman, Lynn (ISIM Series on Contemporary Muslim Societies, 2007)
A number of Arab states have recently either codified Muslim family law for the first time, or have issued amendments or new laws which significantly impact the statutory rights of women as wives, mothers and daughters. In Women and Muslim Family Laws in Arab States Lynn Welchman examines women's rights in Muslim family laws in Arab states across the Middle East while also surveying the public debates surrounding the issues. The author considers these new laws alongside older statutes to comment on the patterns and dynamics of change both in the texts of the laws, and in the processes through by which they are drafted and issued. She draws on original legal texts and explanatory statements as well as on extensive secondary literature particular to certain states for an insight into practice, and on; interventions by women's rights organizations and other parties to the debate in the press and in advocacy materials. The discussions are set in the contemporary global context that 'internationalises' the domestic and regional debates. The book considers laws in states from the Gulf to North Africa in regard to their approaches to issues of codification processes and issues of and of registration, capacity and guardianship in marriage, polygyny, the marital relationship, divorce and child custody. It has a full bibliography and includes an annex providing translated extracts of the laws under examination.